Technology audit of the Technological University of the Philippines-Taguig Campus Learning Resource Center (TUPT-LRC) - Miranda, Danilo M.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2010)
This study entitled Technology Audit of TUP-Taguig Campus Learning Research Center was created in order to raise the level of academic competency of the university campus in the field of Science and Technology. This study is very vital for the organization to determine whether TUPT-LRC is leading to ICT Information and Communication Technology (ICT). Interviews conducted and subsequent assessment of the different areas facilitated the avenue for the University to discover the present conditions in terms of the technology capability of the TUP-Taguig LRC. Findings of the study reveal that it is very evident that TUPT-LRC is presently experiencing insufficiency in mostly of the 11 (eleven) different areas that was audited. These short comings can be improved by a methodical way of assessing its present situation and augment its present resources available to be at par with other State and Private Universities. It discovered that there was a great disparities in eleven (11) areas of TUPT_LRC as compares to ILS-UPD and the Library of De Lasalle Taft. Every area were carefully study, which made this project of great help in assisting the administration in its medium and long term plans (5 to 10 and 10 to 15 years plans) and its other targets as it was anchored to its Mission and Vision of the university.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Technological University of the Philippines-Taguig.; Campus Learning Resource Center (TUPT-LRC); Technology -- management; Technology audit